Satisfaction of nurses with a training course for the operationalization of protocol on pressure ulcers - Santos, Mayara Vasconcelos; Cerqueira, Phamela Vieira; Moura, Elaine Cristina Carvalho; Silva, Grazielle Roberta Freitas da; Falcão, Lariza Martins (Rev Rene, 2015)
Objective: to identify the degree of satisfaction of nurses with a training course for operationalization of protocol on pressure ulcers.  Methods: a descriptive exploratory study made in a philanthropic hospital in the northeast of Brazil. An instrument on satisfaction was applied to 21 participant nurses of the course on pressure ulcer based on care protocol. Results: young adults predominated (23-33 years old), female (87.5%), with significant participation in events, courses and research activities (81.0%), and 19.0% of research publication. The overall rate of satisfaction with the course made at the workplace was 84.34%. Conclusion: when the fundaments of practice based on evidence were cleared, the rate of satisfaction of the professionals who participate in Permanent Education activities is high, which makes clinical protocol operationalization possible.